College Algebra (10th Edition)

Published by Pearson
ISBN 10: 0321979478
ISBN 13: 978-0-32197-947-6

Chapter 9 - Section 9.1 - Sequences - 9.1 Assess Your Understanding: 49

Answer

$$\sum_{k=1}^{n}(k+2) = \dfrac{n(n+1)}{2} + 2n$$

Work Step by Step

RECALL: For any constant $c$, (1) $$\sum_{k=1}^{n}(k+c) = \sum_{k=1}^{n}k + \sum_{k=1}^{n}c$$ (2) $$\sum_{i=1}^{n}c = nc$$ (3) $$\sum_{k=1}^{n}k = \dfrac{n(n+1)}{2}$$ Using rule (1) above gives: $$\sum_{k=1}^n(k + 2) = \sum_{k=1}^{n}k + \sum_{k=1}^{n}2$$ Use rule (3) and rule (2) above, respectively, to obtain: $$\sum_{k=1}^{n}k + \sum_{k=1}^{n}2 = \dfrac{n(n+1)}{2} + 2n$$ Thus, $$\sum_{k=1}^{n}(k+2) = \dfrac{n(n+1)}{2} + 2n$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.